Bioimprint Replication for Cancer Research Investigations and its Analysis Using Artificial Neural Network - Fahmi, Samsuri; N., Vigneswaran; Balu, Ranganathan (2014)
In this paper, we have described about the obtaining of high resolution image of abnormal cells and the analysing it through artificial neural network (ANN). High resolution images can be obtained through imprinting method. High resolution imaging techniques like AFM, SEM and TEM can be used. These cell replicas contain features related to the cancer which can be used to train the neural network Further it can be used for autonomous classification of cancerous and noncancerous cells.